1959
DOI: 10.1113/jphysiol.1959.sp006193
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on the preparation, purification and nature of irin

Abstract: Distilled water extracts of rabbit iris contain an acid which is physiologically active on certain smooth muscles (Ambache, 1957a). Improvements in the purification and assay of this substance are now described and also an investigation of its chemical nature. First, a number of acids of biological origin have been screened for activity. Although representative of a variety of structuretypes, the acids examined are nearly all inactive or can be otherwise distinguished from irin. Direct evidence is then produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

1968
1968
1984
1984

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 34 publications
1
30
1
Order By: Relevance
“…The present observations may be related to the increased protein content of the aqueous humour in the eyes which received prostaglandins, since Duke-Elder & Duke-Elder (1931) observed that the IOP in the rabbit became refractory to repeated mechanical stimulation of the iris, and Ambache (1959) showed that protein may interfere with the action of irin on the hamster colon. Thus, the presence of plasma proteins in the aqueous humour may curtail the action of intracamerally administered prostaglandin.…”
Section: Discussionmentioning
confidence: 91%
“…The present observations may be related to the increased protein content of the aqueous humour in the eyes which received prostaglandins, since Duke-Elder & Duke-Elder (1931) observed that the IOP in the rabbit became refractory to repeated mechanical stimulation of the iris, and Ambache (1959) showed that protein may interfere with the action of irin on the hamster colon. Thus, the presence of plasma proteins in the aqueous humour may curtail the action of intracamerally administered prostaglandin.…”
Section: Discussionmentioning
confidence: 91%
“…A poststimulatory inhibition of acetylcholine release in the presence of eserine was also found at higher frequencies (0 1 and 0 5 Hz), but it was not so marked. Ambache (1957Ambache ( , 1959 extracted from iris tissue a pharmacologically active material which he called irin. This material is now thought to contain prostaglandin (Waitzman, Bailey & Kirby, 1967).…”
Section: Pmentioning
confidence: 99%
“…3, are recovered from the ether phase (Ambache, 1957(Ambache, , 1959. The residues of the evaporated ether phases will be referred to as ether-purified irins, and their doses will be given in -mg of original tissue.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…3, as described previously (Ambache, 1959;Ambache, Reynolds & Whiting, 19%3). The ether phases were evaporated in a stream of nitrogen and the residues obtained in this way were dissolved in 0.9% NaCl solution and subdivided into samples, some of which were treated with the reagent (100 mg/ml.)…”
Section: Prostaglandins and Girard's Reagent Tmentioning
confidence: 99%
See 1 more Smart Citation